Oxacycle‐Fused [1]Benzothieno[3, 2‐b][1]benzothiophene Derivatives: Synthesis, Electronic Structure, Electrochemical Properties, Ionisation Potential, and Crystal Structure. Issue 9 (2nd November 2018) - Mohankumar, Meera; Chattopadhyay, Basab; Hadji, Rachid; Sanguinet, Lionel; Kennedy, Alan R.; Lemaur, Vincent; Cornil, Jérôme; Fenwick, Oliver; Samorì, Paolo; Geerts, Yves
Abstract: The molecular properties of [1]benzothieno[3, 2‐ b ][1]benzothiophene (BTBT) are vulnerable to structural modifications, which in turn are determined by the functionalization of the backbone. Hence versatile synthetic strategies are needed to discover the properties of this molecule. To address this, we have attempted heteroatom (oxygen) functionalization of BTBT by a concise and easily scalable synthesis. Fourfold hydroxy‐substituted BTBT is the key intermediate, from which the compounds 2, 3, 7, 8‐bis(ethylenedioxy)‐[1]benzothieno[3, 2‐ b ][1]benzothiophene and 2, 3, 7, 8‐bis(methylenedioxy)‐[1]benzothieno[3, 2‐ b ][1]benzothiophene are synthesized. The difference in ether functionalities on the BTBT scaffold influences the ionisation potential values substantially. The crystal structure reveals the transformation of the herringbone motif in bare BTBT towards π‐stacked columns in the newly synthesized derivatives. The results are further justified by the simulated HOMO levels of the model compound. Abstract : Tuned electronics : The critical role of heteroatom modification on the [1]benzothieno[3, 2‐ b ][1]benzothiophene (BTBT) backbone is addressed by fourfold oxy‐functionalization. The molecular properties of oxacycle fused BTBT derivatives have been detailed which is further compared with the bare BTBT.